The Important Role of Management Accounting in Optimizing Cost Control and Improving Profitability in the Service Sector - Dessy Evianti; Rachmawaty Rachman; Sri Imaningati; Muhammad Yusuf (PT. Anagata Sembagi Education, 2024)
Management accounting plays a very important strategic role in improving the profitability of the service sector. Its function goes beyond the mere recording of financial transactions to include analyzing and managing operational costs with a critical and in-depth approach. Through techniques such as activity-based costing, companies can accurately identify key cost sources and implement more effective control measures. The results of this analysis allow companies to set more competitive prices, increase profit margins, and maximize operational efficiency. Management accounting provides data and insights that are essential for strategic decision-making. Accurate information on financial and operational performance enables management to assess the effectiveness of various business initiatives, including new product development and market expansion. This critical analysis helps identify areas where efficiency can be improved and costs can be reduced, thereby supporting long-term strategies for sustainable growth. The integration of management accounting principles into the operational strategies of service companies enables them to face the challenges of a dynamic market, improve competitiveness, and achieve sustained profitability. Management accounting not only helps in cost control but also makes a significant contribution in improving the quality of decision making and strategic planning. A suitable approach for companies can achieve better financial and operational goals, ensuring sustainability and steady growth in an increasingly competitive business environment. Management accounting, thus, is a tool that not only supports efficiency but also encourages innovation and strategic adaptation critical for long-term success.